Gravitational waves as the probe of early universe - Yükselci, Ahmet Emrah (Graduate School, 2024)
The study of gravitational waves has recently become more and more important especially after their direct detection, since they have the potential to provide information about own sources due to their weakly interacting nature, which may allow them to remain almost intact even from processes of the early Universe and to contribute to the "Stochastic Gravitational Wave Background" today. The main purpose of this thesis is to examine the first-order cosmological phase transitions and the gravitational waves as the remnants of these processes by virtue of numerical simulations. To this end, firstly, the non-minimally coupled scalar field model is examined in the context of first-order cosmological phase transitions in order to determine the possible effect of the coupling parameter on the process. Then, the other section of the thesis is devoted to investigation of the mutual effects between the expansion of the Universe and the phase transition, together with the inspection of anisotropy through the energy density parameter of the shear scalar by implementing the Bianchi Type-I metric to the model, which contains a minimally coupled scalar field as the order parameter of the transition.
Erken evrenin kütleçekim dalgaları ile incelenmesi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2024
Keywords: gravitational waves; kütleçekim dalgaları